2022
DOI: 10.1073/pnas.2205881119
|View full text |Cite
|
Sign up to set email alerts
|

Single-neuron bursts encode pathological oscillations in subcortical nuclei of patients with Parkinson’s disease and essential tremor

Abstract: Deep brain stimulation procedures offer an invaluable opportunity to study disease through intracranial recordings from awake patients. Here, we address the relationship between single-neuron and aggregate-level (local field potential; LFP) activities in the subthalamic nucleus (STN) and thalamic ventral intermediate nucleus (Vim) of patients with Parkinson’s disease ( n = 19) and essential tremor ( n = 16), respectively. Both disorders have been characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 72 publications
1
15
1
2
Order By: Relevance
“…After observation of spatial selectivity in thalamocortical INS, we sought to control small neural populations through closed-loop feedback. Current adaptive DBS systems used in Parkinson’s disease use relatively simple control algorithms centered around reducing β band biomarker correlates of symptomology using single or dual threshold “thermostatic” control(42, 75, 76) which may interfere with activities such as volitional movement(42) and may potentially occlude oscillatory neural dynamics unrelated to disease(39). Control of smaller populations of neurons relevant to disease with control algorithms that encode subject specific firing dynamics may provide targeted treatment and a reduction in off-target side effects.…”
Section: Resultsmentioning
confidence: 99%
“…After observation of spatial selectivity in thalamocortical INS, we sought to control small neural populations through closed-loop feedback. Current adaptive DBS systems used in Parkinson’s disease use relatively simple control algorithms centered around reducing β band biomarker correlates of symptomology using single or dual threshold “thermostatic” control(42, 75, 76) which may interfere with activities such as volitional movement(42) and may potentially occlude oscillatory neural dynamics unrelated to disease(39). Control of smaller populations of neurons relevant to disease with control algorithms that encode subject specific firing dynamics may provide targeted treatment and a reduction in off-target side effects.…”
Section: Resultsmentioning
confidence: 99%
“…It is still debated whether intrinsic pacemaker activity of single focus generates the abnormal β synchronous oscillations, or it is generated by more complex network activity 23‐25 . Because certain evidences indicate that the cortex is critically involved in the generation of this pathological activity, 26,27 we initially hypothesized that β oscillatory activity would not be identical between groups.…”
Section: Discussionmentioning
confidence: 99%
“…22 It is still debated whether intrinsic pacemaker activity of single focus generates the abnormal β synchronous oscillations, or it is generated by more complex network activity. [23][24][25] Because certain evidences indicate that the cortex is critically involved in the generation of this pathological activity, 26,27 we initially hypothesized that β oscillatory activity would not be identical between groups. This assumption was based on knowledge regarding the cortical sparing in PRKN-PD that contrasts the extensive cortical involvement in GBA-PD (demonstrated also in this study by more severe cognitive impairments).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beta oscillations in LFP recordings play a role in the temporal dynamics of high frequency oscillations (HFOs) 16, 17 . A recent study reported that periodic single-neuron bursts in the STN commonly preceded the LFP oscillation (13∼33 Hz), but that other neuronal firing activity had no relationship to the LFP 18 .…”
Section: Introductionmentioning
confidence: 99%